The moral and political philosophy of immigration : liberty, security, and equality / José Jorge Mendoza. - Mendoza, José Jorge (Lexington Books, 2017)
In this book, José Jorge Mendoza argues that the difficulty with resolving the issue of immigration is primarily a conflict over competing moral and political principles and is thereby, at its core, a problem of philosophy. Using philosophical resources, this book provides some normative guidance to future immigration policy and reform. --